A HIGH THROUGHPUT MASS SPECTROMETRIC ASSAY FOR DISCOVERY OF HUMAN LIPOXYGENASE INHIBITORS AND ALLOSTERIC EFFECTORS - Jameson, J. Brian (Anal Biochem, 2015)
Lipoxygenases (LOX) regulate inflammation through the production of a variety of molecules whose specific downstream effects are not entirely understood due to the complexity of the inflammation pathway. The generation of these biomolecules can potentially be inhibited and/or allosterically regulated by small synthetic molecules. The current work describes the first mass spectrometric, high throughput method for identifying small molecule LOX inhibitors and LOX allosteric effectors, which change the substrate preference of human lipoxygenase enzymes. Using a volatile buffer and an acid-labile detergent, enzymatic products can be directly detected using liquid chromatography-mass spectrometry (HPLC-MS), without the need of organic extraction. The method also reduces the required enzyme concentration compared to traditional UV absorbance methods by approximately 30-fold, allowing accurate binding affinity measurements for inhibitors with nanomolar affinity. The procedure was validated using known LOX inhibitors and the allosteric effector, 13(S)-hydroxy-9Z,11E-octadecadienoic acid (13-HODE).